Studi Kasus Pengaturan Green Banking dalam Peraturan Perundang-Undangan Indonesia: Peluang dan Tantangan - Arista Nadiariani; Naura Fairusyifa Tridewo; Kasyifa Alifya Anfasha; Diffa Aulia Putri Syadena; Dahlia Bunga Rembulan; Lindryani Sjofjan (Jurnal Hukum Lex Generalis, 2025)
Green banking regulation in Indonesia remains sectoral and lacks a comprehensive legal framework, relying on instruments like POJK No. 51/2017 and Presidential Regulation No. 59/2017. Key challenges include weak legal enforcement, supervision, inter-agency coordination, and the risk of greenwashing. Nevertheless, green banking holds significant potential to support the transition toward Net Zero Emission by 2060. Strategic steps are needed, including the establishment of specific laws, regulatory strengthening, policy harmonization, provision of incentives, and capacity building to achieve inclusive and sustainable green economic development.